The Influence of Macroeconomics as a Determinant of Capital Structure in Information Technology Companies Listed on the Indonesia Stock Exchange - Syah, Silvana (Journal of Business and Behavioural Entrepreneurship, 2025)
This study aims to analyze the influence of macroeconomic variables as determinants of the capital structure of information technology companies listed on the Indonesia Stock Exchange. The population for this study consists of information technology sector companies listed on the Indonesia Stock Exchange between 2020 and 2023. The research sample was obtained using a purposive sampling method, totaling 22 companies. The capital structure is proxied by the Debt to Equity Ratio (DER). The determinants of the capital structure in this study include inflation, gross domestic product growth, interest rates, and profitability. Based on the results of the fixed effects panel regression analysis, it was found that macroeconomic variables such as GDP, inflation, interest rates, and exchange rates do not have a significant impact on the capital structure of companies in this industry. GDP, inflation, and interest rates do not show a significant influence on the capital structure of information technology companies. This suggests that capital structure decisions in this industry are more influenced by other factors. The information technology industry may be more affected by market dynamics, technological innovation, access to equity funding, and unique management strategies. The negative average profitability indicates that companies in this industry face significant financial challenges, but this does not directly affect their capital structure.